Virtual Debate Platforms for Enhancing Critical Thinking, Speaking Fluency, and Argumentation Skills in ESL Classrooms - Dedi Gunawan Saputra; Dewi Suryaningsih Saputri; Siti Fatimah Abd. Rahman (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study investigates the effectiveness of virtual debate platforms in enhancing English as a Second Language (ESL) learners’ critical thinking, speaking fluency, and argumentation skills. The research was conducted using a quasi-experimental design with intermediate-level ESL students as participants. Data were collected through critical thinking tests, speaking fluency rubrics, and argumentation rubrics, complemented by qualitative analysis of recorded debates. The results indicate significant improvements in students’ critical thinking abilities, fluency in spoken English, and the quality of their arguments, including structure, relevance of evidence, and coherence. Furthermore, virtual debates fostered higher levels of student engagement compared to traditional classroom discussions. These findings underscore the pedagogical potential of integrating technology-based debate activities into ESL instruction, providing interactive and collaborative learning opportunities that address the limitations of conventional teaching methods. The study concludes with recommendations for incorporating virtual debates into ESL curricula and suggests future research on the use of emerging technologies such as artificial intelligence (AI) and virtual reality (VR) to further enhance language learning experiences.